A METHOD FOR MEASURING THE GEOMAGNETIC FLUX MODULUS - Yakupov V.S.; Yakupov S.V. (My University, 2002)
A method is proposed for measuring the modulus of the geomagnetic flux through an arbitrary contour on the Earth''s surface and its relatively slow variations with the help of a multicoil loop, the number of its coils varying continuously with time at a constant rate without breaking the loop.
Keywords: GEOMAGNETIC FLUX; OBSERVATION; MEASURING